A nitrocefin-based amperometric assay for the rapid quantification of extended-spectrum β-lactamase-producing Escherichia coli in wastewaters. (1st February 2017) - Chantemesse, Benoît; Betelli, Laetitia; Solanas, Sébastien; Vienney, Fabienne; Bollache, Loïc; Hartmann, Alain; Rochelet, Murielle
Abstract: A sensitive and inexpensive amperometric assay based on the electrochemical detection of the β-lactamase activity using the nitrocefin as substrate was developed for the rapid and quantitative detection of extended spectrum beta-lactamase-producing Escherichia coli (ESBL-EC) in urban wastewaters. The specific detection of ESBL-EC was achieved by culturing the filtered sample in a medium containing the cefotaxime supplemented or not with the potassium clavulanate inhibitor. This step was followed by the incubation of each subculture filtrate with the nitrocefin substrate which hydrolysis was monitored by amperometry using disposable carbon screen-printed sensors. Current intensities iCef and iClav correspond to the intensity of the anodic current measured (∼+ 0.2 V vs . Ag/AgCl) for the sample incubated with the cefotaxime without and with potassium clavulanate, respectively. The intensity value i = iCef – iClav was chosen as the analytical response. ESBL-EC calibration plots were established with artificially contaminated wastewater samples. This assay allowed the detection of ESBL-EC amounts as low as 10 cfu in treated effluents and 100 cfu in raw wastewaters with short time analysis of 5.5 h and 4.5 h, respectively. The amperometric method was applied to the analysis of 38 wastewater samples and the results were in good agreement with CFU counts on a selective chromogenic medium for 24 h. Owing to its rapidity, convenience, low-cost and portability, this assay is a promising tool to obtain quantitative data on antimicrobial-resistant E. coli in wastewater effluents. Furthermore, this assay might be used to improve wastewater treatment plant processes in order to minimize the release of antibiotic resistant bacteria into the aquatic environment. Graphical abstract: Highlights: A specific amperometric assay involving the nitrocefin substrate and disposable carbon sensors. The rapid (<5h30) and quantitative detection of extended-spectrum β-lactamase (ESBL) activity in wastewaters. Calibration of the method with sterilized wastewater samples spiked with ESBL-producing E. coli . Good correlation between the electrochemical detection and the culture-based enumeration for wastewater monitoring.